Ethnobotany, pharmacology, phytochemistry and medicinal uses of Huamanpinta - Chuquiraga spinosa Less. (Asteraceae) in Peru - Perez-Chauca, Enma; Saldaña-Bobadilla, Vanessa; Minchan-Herrera, Patricia (Ethnobotany Research and Applications, 2020)
Background: Chuquiraga spinosa Less., Known as "Huamanpinta", is an important medicinal plant in conventional medicine for the treatment of various diseases such as disorders of the urinary system, vaginitis and vaginal infection, renal and prostate inflammation, prostate cancer, diuretic and sexual impotence. This review article documents current information on C. spinosa, including ethnobotanical studies, medicinal uses, phytochemical composition, pharmacological activities, toxicity, and commercialization. Methods: All the information provided on C. spinosa was compiled using electronic databases GoogleScholar, Scopus, PubMed and ScienceDirect. Results and discussion: A total of 338 documents were registered, of which 49 met the eligibility criteria. Phytochemical studies on C. spinosa revealed the presence of chemical compounds such as: flavonoids, phenolic compounds, saponins, alkaloids, tannins, terpenes and steroids. The alcoholic extracts of the aerial parts of C. spinosa showed various activities in vitro and in vivo such as antioxidant, anti-inflammatory, antifungal, immunomodulatory and protective activity against metabolic syndrome and hypercholesterolemia. C. spinosa revealed to have a therapeutic potential as a cytotoxic agent against various cancer cell lines. Conclusions: Despite the therapeutic potential reported in the literature on this species, the biological activities were studied from the alcoholic extracts, the complete mechanisms on which these effects are based are unknown. No studies were conducted to isolate active molecules involved in pharmacological effects. More research evaluating this activity and clinical studies should be conducted to demonstrate its role as an anticancer agent in the future. Keywords: Traditional medicine, medicinal plants, EsSalud, North of Peru.